Evaluating the Association of Regional and City-Level Environmental Greenness and Land Over Patterns With PM2.5 Pollution: Evidence From the Shanxi Province, China - Guo, Guangxing; Liu, Liwen; Duan, Yonghong (Frontiers in Environmental Science, 2022)
Ambient fine PM2.5 (particulate matter with aerodynamic diameters ≤2.5 μm) has been a major threat to human health. Fates and exposure to PM2.5 can be affected by various factors, and environmental greenness have been documented to be significantly associated with the exposure disparities. However, the relationship between the greenness and ambient PM2.5 on the region and city levels, and variations across different land cover types is still not well understood. In this study, we investigated the spatiotemporal patterns of land cover and environmental greenness in Shanxi, north China and their relationships with PM2.5 changes from 2001 to 2020 varying over different land cover types and cities. The results showed under the socioeconomical development in the past two decades, the area of cropland and grassland was decreasing while the woodland and built-up land were increasing. The mean annual NDVI of the study area showed a significant increasing trend (P<0.01), while the annual PM2.5 concentration decreased. The same trends were observed across different land cover types and cities. The annual average of PM2.5 concentration had a significantly negative correlation with the mean annual NDVI (R=-0.723, P<0.01). This association was enhanced with the decrease of vegetation greenness and the increase of built-up land proportion, indicating that in construction land with frequent human activities, especially in built-up areas with low vegetation coverage, improving environmental greenness can effectively reduce PM pollution; however, the reduction effect of greenness on PM2.5 is lower in the high green space coverage areas than in low green space coverage areas. These results provide quantitative decision-making references for the rational development, utilization and management of land resources, but also achieving regional coordinated controls of PM2.5 pollution by optimizing land use.